American traitor - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2021)
"Pike Logan must pull two major world powers back from the brink of war in the latest pulse-pounding thriller from New York Times bestselling author and former Special Forces officer Brad Taylor"--